Indonesia economic crisis : diagnosis and prognosis. - Shen, Bing. (2008)
The purpose of this paper is to find out what are the reasons that caused the Indonesia’s recent economic crisis, and present some possible solutions to it. The paper is done by intensive research and is applied with economic analysis.